PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE LEARNING CELL DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 11 PADANG - Gustina, Widya; Husna, Husna; Pratiwi, Merina (Pendidikan Matematika, 2013)
This research is introduction by the lack of the studentsâ understanding of mathematical concept and the mathematics learning activities by teacher center. This research is aims to determine Â the implementation of active learning strategy type The Learning Cell in improving studentsâ understanding of mathematical concept class VIII SMPN 11 Padang. The type of research is experiment with random of subject. Population in this research is students class VIII SMPN 11 Padang who registered in academic year 2012/2013. The technique of sampling is random and selected class VIIIF as an experimental class and VIIIE as a control class. Instrument used was an essay test with a reliability test is 0,826. Based on the analysis of data obtained that the average student learning outcomes experimental class is greater than the control class. Hypothesis testing using one side of t-test with the MINITABâS program, obtained P-value is less than Î±. The hypothesis is accepted at the 95% confidence level. Thus it can be concluded that the studentsâ understanding of mathematical concept with an active learning strategy type The Learning Cell is better than studentsâ understanding of mathematical concept by implementing conventional learning class VIII SMPN 11 Padang.